Improving reliability and quality for product success - Dongsu ryu (CRC, 2012)
For almost every sensationalized media report of product failure, a closer look often determines these failures occurred due to inadequate reliability theory and methodology. Current theories and practices cannot solve these problems, mainly because test specifications, especially lifetime tests, express their results as either pass or fail; these results thus provide little useful quantitative information. In a clear, concise presentation, Improving Reliability and Quality for Product Success discusses how to eradicate failures in hardware products and, consequently, achieve greater success ..